2013
DOI: 10.3348/kjr.2013.14.2.375
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Characteristics of Stage I Non-Small Cell Lung Cancer on CT and FDG-PET: Relationship with Epidermal Growth Factor Receptor Protein Expression Status and Survival

Abstract: ObjectiveTo identify CT and FDG-PET features associated with epidermal growth factor receptor (EGFR) protein overexpression, and to evaluate whether imaging features and EGFR-overexpression can help predict clinical outcome.Materials and MethodsIn 214 patients (M : F = 129 : 85; mean age, 63.2) who underwent curative resection of stage I non-small cell lung cancer, EGFR protein expression status was determined through immunohistochemical analysis. Imaging characteristics on CT and FDG-PET was assessed in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 32 publications
0
27
1
6
Order By: Relevance
“…Spiculated or lobulated margins are findings of malignant pulmonary nodule [16]. Lobulated margin was found in 76.6% and 62.5% of the tumours in a study of stage I non-small cell lung cancer (NSCLC) [13] and a study of peripheral adenocarcinoma no greater than 2 cm in diameter [17], respectively. In these studies, lobulated margin was not related to survival.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Spiculated or lobulated margins are findings of malignant pulmonary nodule [16]. Lobulated margin was found in 76.6% and 62.5% of the tumours in a study of stage I non-small cell lung cancer (NSCLC) [13] and a study of peripheral adenocarcinoma no greater than 2 cm in diameter [17], respectively. In these studies, lobulated margin was not related to survival.…”
Section: Discussionmentioning
confidence: 98%
“…FDG PET (Allegro, Philips Medical Systems, Cleveland, OH, USA) was performed in 11 patients, and integrated FDG PET/CT was performed in 19 patients using 3 different PET/CT cameras: Discovery BGO (GE Medical Systems) in 1 patient, Gemini (Philips Medical Systems, Cleveland, OH, USA) in 12 and Biograph 40 (Siemens Medical Systems) in 6. The details of the FDG PET or FDG PET/CT imaging have been previously described [12][13][14]. All patients were requested to fast for at least 6 h prior to the FDG PET or FDG PET/CT scan.…”
Section: Fdg Pet Imaging and Interpretationmentioning
confidence: 99%
“…The authors reported that a low EGFR gene copy number was more commonly observed in adenocarcinoma with a GGO of >50%. In 2013, Lee et al (47) reported that tumors with a GGO proportion of >50% were less frequent among tumors with EGFR-overexpression compared with tumors without EGFR-overexpression in 214 patients with stage I NSCLC. Furthermore, in 2011, Hsu et al (48) retrospectively surveyed 162 patients with stage I lung adenocarcinoma with a tumor size of <3 cm, and found that the part-solid and solid pattern tumors had more typical EGFR mutations compared with the pGGO tumors.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR amplification were inversely correlated with the GGO percentage, indeed the frequency of FISH-positivity increased as the proportion of GGO decreased (6,46,47).…”
Section: Molecular Pathology and Ct Featuresmentioning
confidence: 91%